Ion-Pair Spectrophotometric Determination of Sparfloxacin - PATEL, RAKESH; KUMAR, BRIJESH; SHANKAR SHUKLA, SHIV; SINGH , RAGHVENDRA; BHANDARI, ANIL (Asian Journal of Chemistry, 2010)
A method was developed for the quantitative estimation of sparfloxacin in tablets. The method is based upon the reaction of sparfloxacin with methyl orange, forming a yellow coloured complex, which is extracted in chloroform and analyzed. The absorbance maxima (λmax) was found to be 390.8 nm. Optimization of the reaction was carried out with factors such as buffer strength, stability of complex, molar ratio of drug : dye and extraction time. The proposed method was validated as per ICH guidelines. The recovery studies confirmed the accuracy and precision of the method.